Mating-induced increase in Kiss1 mRNA expression in the anteroventral periventricular nucleus prior to an increase in LH and testosterone release in male rats - Youki WATANABE; Kana IKEGAMI; Sho NAKAMURA; Yoshihisa UENOYAMA; Hitoshi OZAWA; Kei-ichiro MAEDA; Hiroko TSUKAMURA; Naoko INOUE (The Journal of Reproduction and Development, 2020)
Kisspeptin has an indispensable role in gonadotropin-releasing hormone/gonadotropin secretion in mammals. In rodents, kisspeptin neurons are located in distinct brain regions, namely the anteroventral periventricular nucleus-periventricular nucleus continuum (AVPV/PeN), arcuate nucleus (ARC), and medial amygdala (MeA). Among them, the physiological role of AVPV/PeN kisspeptin neurons in males has not been clarified yet. The present study aims to investigate the acute effects of the olfactory and/or mating stimulus with a female rat on hypothalamic and MeA Kiss1 mRNA expression, plasma luteinizing hormone (LH) and testosterone levels in male rats. Intact male rats were exposed to the following stimuli: exposure to clean bedding; exposure to female-soiled bedding as a female-olfactory stimulus; exposure to female-soiled bedding and mating stimulus with a female rat. The mating stimulus significantly increased the number of the AVPV/PeN Kiss1 mRNA-expressing cells in males within 5 minutes after the exposure, and significantly increased LH and testosterone levels, followed by an increase in male sexual behavior. Whereas, the males exposed to female-soiled bedding showed a moderate increase in LH levels and no significant change in testosterone levels and the number of the AVPV/PeN Kiss1 mRNA-expressing cells. Importantly, none of the stimuli affected the number of Kiss1 mRNA-expressing cells in the ARC and MeA. These results suggest that the mating-induced increase in AVPV/PeN Kiss1 mRNA expression may be, at least partly, involved in stimulating LH and testosterone release, and might consequently ensure male mating behavior. This study would be the first report suggesting that the AVPV/PeN kisspeptin neurons in males may play a physiological role in ensuring male reproductive performance.